2021
DOI: 10.1093/jcbiol/ruab052
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and reproduction in the Hapalocarcinus marsupialis Stimpson, 1859 species complex (Decapoda: Brachyura: Cryptochiridae)

Abstract: Symbiotic relationships contribute considerably to the high biodiversity found on coral reefs. Coral-dwelling gall crabs (Cryptochiridae) represent a prime example of coral-associated invertebrates that exhibit obligate relationships with their host. The induction of a skeletal modification in the coral, used as a dwelling by the crab, is the most remarkable aspect of this close association. Here we examined Hapalocarcinus marsupialisStimpson, 1859, collected from Pocillopora and Stylophora corals in the Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…These values are comparable with threshold values previously reported for thoracotreme crabs (1.49%-6.25%), from studies of groups in which taxonomy is relatively well resolved, and the examined taxa show discrete morphologies (see Davie et al, 2010;Shih et al, 2012Shih et al, , 2019KJH Wong et al, 2012). However, cryptochirid taxonomy is nowhere well resolved in two sense: numerous previously unrecognized species-level taxa (Wei et al, 2016;Bähr et al, 2021;Xu et al, 2021; see below) and previous morphology-based generic placement insufficient in encapsulate true species richness, thus rendered composite (van der Meij and Nieman, 2016; see Remarks under L. doughnut above). As such, both our intra-and interspecific distance values show considerable range of variation and are probably inflated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are comparable with threshold values previously reported for thoracotreme crabs (1.49%-6.25%), from studies of groups in which taxonomy is relatively well resolved, and the examined taxa show discrete morphologies (see Davie et al, 2010;Shih et al, 2012Shih et al, , 2019KJH Wong et al, 2012). However, cryptochirid taxonomy is nowhere well resolved in two sense: numerous previously unrecognized species-level taxa (Wei et al, 2016;Bähr et al, 2021;Xu et al, 2021; see below) and previous morphology-based generic placement insufficient in encapsulate true species richness, thus rendered composite (van der Meij and Nieman, 2016; see Remarks under L. doughnut above). As such, both our intra-and interspecific distance values show considerable range of variation and are probably inflated.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of host specificity can be confounded by unrecognized diversity. Recent investigations on H. marsupialis, a species distributed from western Indian Ocean to the Central Pacific (Wei et al, 2016;Bähr et al, 2021), showed important implications. Despite highly conserved morphologies, genetic data based on materials amassed across the distribution range recognize multiple putative species, each biologically distinct (COI divergences range from 3.2% to 15.7%; Bähr et al, 2021), and putative species differ in recorded host (of Pocillopora, Seriatopora, and Stylophora; Wei et al, 2016;Bähr et al, 2021) and early larval characters (Gore et al, 1983).…”
Section: Broad Host Range or Unrevealed Diversity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptochirids occur worldwide, mostly on tropical shallow‐water reefs, but they have also been observed at depths below 500 m (Kropp & Manning, 1987 ). Currently, this family includes 53 species in 21 genera (WoRMS, 2023 ), yet several species complexes have recently been uncovered, and more species are awaiting description (Bähr et al, 2021 ; Xu et al, 2022 ). Gall crabs inhabit a broad range of corals from at least 66 genera (Castro, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their host specificity was used as a scheme to define cryptochirid genera in the past (Fize & Serène, 1957 ), but this has been overhauled by major taxonomic revisions of both corals and crabs (Fukami et al, 2008 ; Huang et al, 2014 ; Kropp, 1990 ; Terraneo et al, 2017 ). With the exception of the generalist species Troglocarcinus corallicola Verrill, 1908, all cryptochirid species are host specific; some at host species level, whereas other crab species associate with one or more closely related coral genera (e.g., Bähr et al, 2021 ; van der Meij, 2015 ; van der Meij et al, 2015 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%